Chemopreventive potential of plant-derived epigenetic inhibitors silibinin and quercetin: an involvement of apoptotic signaling cascade modulation - Ruma Baksi; Rita Rana; Manish Nivsarkar (SpringerOpen, 2021)
Abstract Background Epigenetic deregulation of the cellular apoptotic mechanism is the common hallmark of cancer. Silibinin (SBN) and quercetin (QCT) are two bioflavonoids well known for their epigenetic inhibition property. The objective of the present study was to explore the preventive anti-cancer efficacy of the SBN and QCT in both in vitro as well as in vivo tumor xenograft model through regulating cellular apoptotic signaling pathway. Results SBN and QCT inhibited the growth of A549 and MDA-MB-468 cancer cells in the concentration dependent manner. The treatment caused significant (p < 0.05) reduction of the size and the number of colonies formed by the cancer cells. In vitro apoptosis assay using the fluorescence microscopy revealed that the treatment noticeably increased the percentage of apoptotic cells as compared to the untreated control. Dosing with SBN (200mg/kg), QCT (100mg/kg) alone and in combination was initiated in 3-week-old C57BL6 mice. Interestingly, the treatment prevented tumor progression significantly (p < 0.05) in adult mice without causing any toxicity. Furthermore, SBN and QCT triggered apoptosis via modulating p53 and Bcl2 gene expression and the SOD enzyme activity. Conclusion Daily oral intake of SBN and QCT alone and in combination from the very early stage of life might prevent tumor growth in adult mice through activating cellular apoptotic signaling cascade.